INTERRELATIONS BETWEEN ACTORS IN TOURISM MANAGEMENT BASED ON THE PENTA HELIX FRAMEWORK : CASE STUDY PASIR PADI BEACH, PANGKALPINANG CITY - Nabilah, Siti Maharani; Alfirdaus, Laila Kholid (Journal of Politic and Government Studies, 2024)
This study was motivated by the lack of good governance in managing Pasir Padi Beach tourism from the perspective of Penta Helix actors. By collecting and analyzing the roles of actors, this thesis discusses the collaborative process that occurred in developing tourism policy at Pasir Padi Beach, as well as the power relations involved. Researchers used qualitative descriptive methods with data collection techniques through observation, interviews, and documentation. This research uses two theoretical frameworks, namely the Collaborative Governance Theory in the Penta Helix and the Power Relations Theory in the Penta Helix. The findings of this research are that there is a relationship between actors in the management of Pasir Padi Beach, which shows that there is a central relationship between the government and the private sector. The existence of power relations in Pasir Padi Beach tourism management policies inhibits private investment, creates uncertainty for the business world, and causes an imbalance of power between the government which focuses on revenue, and the private sector which focuses on profits, excluding main stakeholders such as local communities and academics. Government domination of infrastructure and regulations also influences decision-making, hindering collaboration and transparency. This limited transparency limits participation and hinders collaborative governance, raising sustainability concerns